Kelayakan Usaha Perikanan Bagan Tancap Di Pangkalan Pendaratan Ikan (PPI) Kabupaten Bangka Tengah - Elita Rostianti; Kurniawan Kurniawan; Teguh Ferdinand (Journal of Tropical Marine Science, 2020)
The business of lift net is categorized as pelagic fish catcher. The attempted capture with lift net tool is a potential business with continuous catch and has a high selling price. The purpose of this study is to analyze the feasibility of fishing efforts by using a at Kurau Village Fish Landing Base in Bangka Tengah Regency. This research was conducted in November 2019, in PPI au Central Bangka Regency Province of Bangka Belitung. This research uses survey methods. Quantitative analysis method used is to examine aspects of business feasibility through financial aspect approach using investment eligibility criteria including, Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period (PP). NPV of 11 fishermen is allnaya positive, B/C ratio > 1, PP (Payback Period) is all below 3 years, ROI 125,87 %, and the average IRR value is 70 % greater than the interest value, which means all business capture activities can be feasible continued.